A Study to Assess the Effectiveness of Video-assisted Teaching Program on Knowledge Regarding Selected Emergency Pre-cardiac Medications among Staff Nurses at Selected Hospital in Bangalore - Suresh, R. (Indian Journal of Nursing Sciences, 2024)
Background: Coronary heart disease is now the leading cause of mortality worldwide and accounts for the death of 3.8 million men and 3.4 million women each year. In developing countries, coronary artery diseases have been recognized as a major public health problem. Cardiovascular emergencies account for at least 30% of all medical emergencies. During cardiovascular emergencies, the survival of the patient depends on a rapid response that provides high quality treatment based on latest guideline. Administration of the correct drugs is an important aspect of this process and among the health team members nurses are taking an increasingly important role. However, most of the studies done by the various researchers found that the majority of the nurses are unaware about the vital drugs used in the cardiac emergencies. Methods: In the present study, one group pre-test and post-test research design was used to assess effectiveness of video-assisted teaching program (VATP) on knowledge of emergency drugs among 30 staff nurses by purposive sampling method working in selected hospital. Structured knowledge questionnaire was used. Results: Finding revealed that the majority of respondents 70% had only average knowledge whose percentage of score ranged between (35 and 70). Only 10% of the respondents had good knowledge (70–100) and 20% of the respondents had poor knowledge (0–35) regarding emergency drugs. Conclusion: Finding of the study showed that the post-test knowledge scores showed a significant increase in knowledge. The research was conducted with the VATP improved knowledge of the staff nurses on emergency drugs.